Resistant bugs, porous borders and ecologies of care in India. (January 2022) - Broom, Alex; Doron, Assa
Abstract: As social science scholarship has routinely illustrated, professional practice is rarely as contained or coherent as it is often imagined to be. The increasing emphasis on the rise of antimicrobial resistance (AMR) has drawn renewed attention to the interconnectedness of clinic, community, environment and planet, and how proposed 'solutions' to major problems such as AMR require a broad, cross-cutting lens. In this study, set in Hyderabad, India, we draw on a series of interviews with hospital-based clinicians completed during 2019 and early 2020, to unpack the multidimensional, ecological acceleration of AMR and the implications for everyday practice. Their accounts make visible how practice operates in relation to industrial economies, community vulnerabilities, and ecologies. This in turn highlights the problem of epistemic bordering, where 'sites' of AMR are targeted but are prone to leakage and transgressions. We propose an ecological approach to conceptualising antimicrobial practices with implications for AMR interventions being rolled out in the sub-continent and beyond. Highlights: Examines the nexus of practice and (antimicrobial) resistance in India. Set within the context of India as a hotspot for resistance and drug 'mis-use'. Proposes an ecological rather than behavioural approach to exploring practice. Findings have major implications for how to approach AMR solutions.